2016
DOI: 10.1177/0003702816666288
|View full text |Cite
|
Sign up to set email alerts
|

Direct-on-Filter α-Quartz Estimation in Respirable Coal Mine Dust Using Transmission Fourier Transform Infrared Spectrometry and Partial Least Squares Regression

Abstract: In order to help reduce silicosis in miners, the National Institute for Occupational Health and Safety (NIOSH) is developing field-portable methods for measuring airborne respirable crystalline silica (RCS), specifically the polymorph α-quartz, in mine dusts. In this study we demonstrate the feasibility of end-of-shift measurement of α-quartz using a direct-on-filter (DoF) method to analyze coal mine dust samples deposited onto polyvinyl chloride filters. The DoF method is potentially amenable for on-site anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Although a feasibility study demonstrated 58 m to be packaged within a compact size. The LOD was <1 ppb.…”
Section: Other Instrumental Techniquesmentioning
confidence: 99%
“…Although a feasibility study demonstrated 58 m to be packaged within a compact size. The LOD was <1 ppb.…”
Section: Other Instrumental Techniquesmentioning
confidence: 99%
“…The first successful results on the in-field quantification via the NIOSH direct-on-filter (DoF) method combined with portable FTIR spectrometers have proven to be of comparable quality to the NIOSH 7500 method [21]. In that study, mine dust particles were directly collected onto PVC filters by the respirable samplers [2,22]. The DoF method combined with the FTIR technique is included in ISO 19087:2018 by the International Organization for Standardization [23].…”
Section: Introductionmentioning
confidence: 99%
“…The DoF method combined with the FTIR technique is included in ISO 19087:2018 by the International Organization for Standardization [23]. However, analytical confounders such as variable background and effects of mixed mineral components in the analyzed dust sample matrix have been shown to negatively influence the reliability of the data analysis [1,22,24]. Those effects are most effectively addressed by single variable data evaluation strategies, as shown via a direct calibration approach for coal and non-coal mine dust using partial least squares regression (PLSR) [1,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the field-based estimation of RCS with portable FTIR can provide results comparable to the standard analysis—i.e., XRD analysis with NIOSH 7500—when no analytical confounders are present, [18] the negative effect of other minerals has been recognized as a necessary consideration. [2729] Laboratory methods for RCS quantification uses the experience of analysts and, if needed, pre-treatment of the samples to address the presence of analytical cofounders. These tools will not be available if a portable FTIR is used by industrial hygienists in the field.…”
Section: Introductionmentioning
confidence: 99%